Türkiye’ de 1980- 2001 yılları arasındaki bütçe harcamalarının gelişimi - Güner, Kasım (My University, 2002)
Tezde 1980-2001 yılları arasında Türkiye'deki bütçe harcamalarının gelişimi üç bölüm halinde incelenmiştir. Birinci bölümde kamu harcamalarına ilişkin tanımlar ve yaklaşımlar ile kamu harcamalarının artışına etki eden çeşitli faktörlerden bahsedilmiştir. İkinci bölümde bütçe harcamaları ekonomik ve fonksiyonel sınıflandırmalara göre bir incelemeye tabi tutulmuştur. Ekonomik sınıflandırmaya göre incelediğimiz harcama türlerinden transfer harcamalarının alt kalemleri daha detaylı ele alınmış ve transfer harcamaları içerisinde yer alan faiz giderlerinin bütçe harcamaları içerisinde çok önemli bir yere sahip olduğu görülmüştür. Özellikle iç borç faiz ödemelerinin son yıllarda büyük sıçramalar gösterdiği ve toplam konsolide bütçe harcamalarının yarıdan fazlasını oluşturduğu tespit edilmiştir. İşlevsel ayrımda, ekonomik hizmet amaçlı kuruluşların harcamaları tek başlık altında incelenmiş ve ekonomik sınıflandırmada da yer alan faiz giderleri tekrar incelemeye alınmamıştır. Üçüncü bölümünde ise bahse konu sınıflandırma türlerine göre gelişimi incelenen bütçe harcamaları dönemsel analizlere tabi tutulmuştur. Bu analizde incelenen dönem iki ana gruba ayrılmıştır. Birinci ana grup askeri müdahale yılları olan 1980-1983 arası ile liberal ekonomi politikaların uygulandığı 1984-1990 arası dönem olarak iki alt gruba ayrılmıştır. Bu dönemlerin ilkinde bütçe harcamalarında bir azaltma gayreti olduğu, ikincisinde ise özellikle altyapı yatırım harcamaları dolayısıyla bir artma eğilimi ile fon uygulamalarının ilk defa görülmeye başlandığı yıllar olduğu görülmüştür. İkinci ana grup ise körfez krizi, ekonomik kriz, Marmara depremi gibi kriterlere göre, üç alt gruba ayrılmış ve yapılan incelemeler neticesinde bu dönemlerde de bütçe harcamalarında gittikçe belirginleşen artışların olduğu görülmüştür.

In the thesis, between 1980 and 2001 years, the developments of the budget expenditure in Turkey have been examined in three chapters. In the first chapter, it has been talked about the definitions and the opinions of the public expenditures, and different factors that effected the public expenditures. In the second chapter, the budget expenditures have been studied according to the economic and the functional classification. The sub parts of the transfer expenditures which concern with the expenditures of the economic classification have been examined more detailed and it has been seen that the interest expenditures which was included by transfer expenditures has a very important position in the budget expenditures. Especially it has been fixed that the internal debt interest payments have shown great increases in the last years and constituted more than half of the consolidated budget expenditures. In functional classification, the organizations that have aimed economic service, have been studied in one title and the interest payments which was also included in economic classification, hasn't studied in this chapter again. In the third chapter, the development of the expenditures that was studied in the classification mentioned above has been analysed as periodic terms. In this analysis, the examined period has been separated into two main parts. The first part also has been separated into 1980-1983 that included the military management term and 1984 - 1990 when applied the liberal economics policy term. In the first of these terms, there has been an endeavour to decrease the budget expenditures, but in the second one it has been especially seen that there has been an increasing tendency in the expenditures of the substructure investments and the applications of fund. The second main group has been classified into the three-sub group according to like as the gulf crisis, the economic crisis and the earthquake in The Marmara and in the end of these studies, it has been seen that there has been manifest increases in these terms too.
Keywords: Bütçe Türkiye; Maliye Türkiye